(untitled) (Actual Problems of Mind, 2022)
Abstract. In the twenty-first century, scholars pay considerable attention to the question of the identity of a person. This category is studied in philosophy, humanities, and social studies. However, there is a question of similarity and differences in the understanding of the term “identity”. Is identity viewed the same in philosophy, sociology, and psychology? The paper attempts to compare the understanding of identity as a category in the mentioned fields of study. First, the article outlines the historical development of identity, sociology, and psychology and the understanding of this category. In analytic philosophy, identity is the question of a person’s existence over time: whether the person at time t1 is identical to a person at time t2. In psychology, identity is regarded as the feeling of being an unchanged subject of thoughts in the stream of consciousness and as the identification with social roles. The first understanding is personal identity. It is viewed the same as in philosophy. The other is social identity. Sociology considers identity predominantly as social identity. Then, the paper compares the understanding of identity in analytic philosophy, psychology, and sociology. In analytic philosophy, personal identity is viewed as logical construction, but the notion of personal identity in psychology is based on the Pure Ego theory. It means identity is a minimal unit and cannot be analyzed further. Social identity is regarded as logical construction. Personal identity in analytic philosophy and social identity in psychology and sociology are based on the same methodological approach, so the paper compares these two categories. As a result of the comparison, some differences have been found in the understanding of the ontological status of the category “identity” and its practical realization.